(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Infection is one of the most important problems in health care services worldwide; also, it constitutes one of the most important causes of morbidity and mortality associated with clinical, diagnostic and therapeutic procedures. Nursing students are more exposed to infections during their clinical training, so they need to improve their performance related to infection control measures. Standard precautions are set of measures formulated to prevent transmission of blood borne pathogens when providing health care. Objective: The objective of this study was to assess nursing students’ knowledge regarding infection control measures and to identify factors affecting adherence to infection control guidelines. Methodology: A cross-sectional study was conducted among 60 graduates at People’s Nursing School Liaquat University Jamshoro. Data were collected using a structured questionnaire consisting of 18 multiple-choice questions related to Infection and Infection Control measures. Data were analyzed using SPSS version 26. Descriptive statistics, including percentages, were used to summarize the data. Results: The study results show 60 participants, with the majority being male 56.67% (n=34), were male, aged between 22–27 years and are in 4thYear of BS Nursing Generic. Out of 60 respondents 34 participants (56.7%) fell within the Good category, 15 participants (25.0%) demonstrated a Moderate level of knowledge and 11 participants (18.3%) were classified in the Poor category. However, notable gaps existed in understanding Infection and Infection Control Measure and recognizing unhygienic practices as a key contributing factor. Conclusion: This study indicates that nursing students generally demonstrate a Good level of competency in infection control practices. However, certain knowledge gaps remain, particularly in areas such as the reporting of needlestick injuries and adherence to consistent hand hygiene protocols. These shortcomings suggest a need for further emphasis on both theoretical understanding and practical application of infection control measures. Addressing these issues is essential to ensure that students are not only knowledgeable about infection control guidelines but are also capable of implementing them effectively in clinical settings.